Different estrus induction protocols and fixed time artificial insemination during the anoestrous period in non-lactating Kivircik ewes - DOGAN, I.; NUR, Z.; KILINC, B. (Journal of the Hellenic Veterinary Medical Society, 2018)
The efficiency of medroxyprogesterone acetate (MAP) sponges or norgestomet ear implants (half or entire) for synchronizing and inducing the estrous cycle in non-lactating Kivircik ewes was investigated during the natural non-breeding period. Ewes were treated for 11 days either with 60 mg MAP sponges (group 1, n=27) or with 1.5 mg norgestomet (group 2, n=25) or with 3 mg norgestomet (group 3, n=27) ear implants. In addition, each ewe received an intramuscular injection of 500 IU of equine chorionic gonadotropin (eCG) and 125 μg cloprostenol (PGF2α), 48 h prior to progestagen removal. Double Cervical Artificial Insemination (AI) with diluted fresh semen was performed at a fixed time (36 and 48 h) following progestagen withdrawal. Mean values for estrous detection rates at the first 12 ± 6 h and within 72 h, the time from progestagen removal to the onset of estrous, the duration of the induced estrous and pregnancy rate were found to be 46.8%, 86.1%, 26.1 ± 7.3 h, 27.0 ± 10.7 h and 27.8%, respectively. There were significant differences between groups 2 and 3 in the time of induced estrous onset (P<0.05). These results indicate that, each of the three protocols was equally efficient in inducing and synchronizing estrus in non-lactating Kivircik ewes during the natural non-breeding period.